Using the Behaviour Change Wheel to develop an intervention to improve conversations about recovery on the stroke unit - Louisa-Jane Burton; Anne Forster; Judith Johnson; Thomas F. Crocker; David J. Clarke (PLoS ONE, 2025)
Background Understanding recovery is important for patients with stroke and their families, including how much recovery is expected and how long it might take. These conversations can however be uncomfortable for stroke unit staff, particularly when they involve breaking bad news. This study aimed to begin development of a novel complex intervention to improve conversations about recovery on stroke units. Methods Informed by previously collected qualitative data, we used the Behaviour Change Wheel (BCW) approach to identify possible 1. barriers to communication about recovery on stroke units; 2. Intervention Functions; 3. Behaviour Change Techniques (BCTs) to incorporate in an intervention. We subsequently sought stroke professionals’ perspectives through an online survey. Respondents rated the importance of barriers for intervention inclusion and evaluated the usefulness and feasibility of the suggested BCTs. Results Our behavioural diagnosis identified a target behaviour of provision of information about recovery by stroke unit professionals to patients and carers. Twelve possible barriers to this behaviour were identified, with six potential Intervention Functions to address them, and 29 BCTs. Forty-eight multidisciplinary professionals responded to the survey. The six barriers rated as most important to address were: lack of confidence; perceptions of insufficient communication skills; lack of knowledge of the benefits; difficulties in deciding when and in what format to provide information; absence of private spaces for discussions; and lack of generic written information to support conversations. The developed intervention strategy comprised twelve clinically feasible and useful BCTs, encompassing the Intervention Functions of Training, Enablement, Persuasion, and Environmental restructuring. Conclusions The BCW approach was successfully used to begin development of an intervention to improve conversations about recovery on the stroke unit; our survey enabled incorporation of stakeholder perspectives. Further development work is required to design intervention materials and test whether the strategies are effective in improving staff and patient outcomes.